Numerical Study of Two Dimensional Steady Incompressible Newtonian Laminar Flow of Blood Through Constricted Artery (European Journal of Pure and Applied Mathematics, 2022)
In this work, a numerical study of two dimensional steady, incompressible Newtonian laminar ow of blood through a stenosed (constricted) artery is investigated. The VariationalIteration Method (VIM) is employed to obtain the analytic expressions for the velocity prole and pressure gradient. The results obtained are graphically discussed for mild stenosis (25%) for low Reynolds number in the range 20{100. The signicance of the analysis is identied by comparing the results obtained with similar studies in existing literature, and established a goodagreement. The results obtained reveal alterations in blood ow due to presence of stenosis in arterial wall and the implications are discussed.